Prospek Pengembangan Padi Gogo Mendukung Lumbung Pangan di Wilayah Perbatasan Pulau Morotai - Saleh, Yopi; Zainiyah, Winda; Yunianti, Ika Ferry (Proceedings Series on Physical & Formal Sciences, 2021)
Upland rice commodity is generally the second choice after paddy in fulfilling community rice needs. Morotai Island is one of the government’s target locations in initiating the Export-Oriented Food Storage program in the Border Region. This study aimed to determined the prospects for the development of upland rice to support food barns in the border region of Morotai Island. The method used is descriptive analysis, measuring the growth rate of rice based on the Compound Annual Growth Rate (CAGR), and measuring the feasibility of farming using income analysis, R/C ratio, and break-even point analysis. The results showed that the increase in the growth rate of harvested area and upland rice production was 25,75 percent with a contribution of 42,81 percent and 31,65 percent, recpectively, of the harvested area and rice production on Morotai Island in the 2011 to 2017 period. Upland rice farming has an R/C ratio of 1.72 which indicated that this farming is feasible. The potential and opportunities for upland rice development to support food barns on Morotai Island are still very prospective. The development of upland rice can be pursued through intensification and extensification of agriculture with the application of cultivation technology, the use of new high yield varieties, increasing the cropping index, and sustainable soil and water conservation efforts. This needs to be supported by strong farmer and extention institutions and easy access for farmers to finance agriculture.